Rubella seroprevalence among primary and pre- primary school pupils at Moi's Bridge location, Uasin Gishu District, Kenya - Tukei Peter; Muchai Paul C; Kombich Janeth J; Borus Peter K (BMC, 2009)
Abstract Background Rubella is an infectious and generally mild childhood viral disease. The disease is of public health importance because infection acquired during early pregnancy often results in foetal abnormalities that are classified as congenital rubella syndrome (CRS). The burden of rubella infection in most developing countries in not well documented because of limited epidemiological data. However, availability of an effective vaccine has made it necessary to have all the countries with no routine vaccination schedule to evaluate the burden of disease in order to make informed decisions on rubella vaccination and strategy. To address this gap we conducted a study to determine age-specific rubella seroprevalence rates and related risk factors among primary and pre-primary school children in Uasin Gishu district, Moi's Bridge location of Kenya. Methods Subjects of the study were 498 pupils from seven primary schools aged 4-20 years. Questionnaire surveys with blood sampling were conducted between January to July 2005. Samples were tested for rubella specific IgG antibody using ELISA test kit (Enzygnost® Behring, Germany). Results Overall, rubella seropositivity rate was 80% and it increased with age from 59% (among ages 4-6 years) to 94% (ages 14-20 years). Multivariate logistic regression analysis model, showed that age of child and ownership of a television set which is a proxy measure of socio-economic status of family were significantly associated with rubella seropositivity. The odds of rubella seropositivity in a child older than 13 years was more than that in children younger than 7 years (OR = 3.8 95% CI 2.56-5.78). The odds of rubella seropositivity in a child whose family did not own a television set was 3 times higher than that of child whose family owned a set (OR 3.06, 95% CI 1.17-7.97). Conclusion The study provides important and highly useful information on rubella age specific seroprevalence rates in Kenya. Advancing age was found to be associated with increased risk of rubella. Low socio-economic factors suggest an increased risk of infection in certain categories of society, and control measures need to target this. Overall, the findings can also be used by policy makers to model introduction of routine rubella vaccination in the country and also other developing countries facing similar challenges. More than half of the children got infected in pre-primary and efforts to control rubella should target pre-school children. These data provides pre-vaccination information that can be used to guide immunization strategy as well as to determine success of an immunization programme.